Growth and yield of maize in t’sen, a local wisdom of planting in one planting hole, typical cropping pattern of West Timor's (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Dimu-Heo YH, Indradewa D, Putra ETS, Purwanto BH. 2022. Growth and yield of maize in t’sen, a local wisdom of planting in one planting hole, typical cropping pattern of West Timor's. Biodiversitas 23: 2502-2511. West Timor farmers have a strategy to anticipate the short rainy season and relatively low rainfall, namely planting maize, cowpeas, and pumpkin together in one planting hole, known as the local wisdom t’sen cropping pattern or t’sen. This study aims to study the growth and yield of maize and obtain maize varieties that are adaptive to the t’sen. The research was conducted at the experimental garden of the Faculty of Agriculture, Universitas Gadjah Mada (UGM), Yogyakarta, from April to August 2019. The study was arranged using a split-plot design with three replications. The t’sen as the main plot consisted of: monoculture maize, maize + cowpea, maize + pumpkin, maize + cowpea + pumpkin, while the varieties as sub-plots consisted of local varieties of maize from Kupang, Timor Tengah Selatan (TTS), Timor Tengah Utara (TTU), Malaka, and superior varieties Lamuru, and Pioneer p35. The results showed that all maize varieties experienced decreased growth and production in the t’sen compared to monoculture. The lowest decrease in growth and yield occurred in one planting hole of maize + cowpea, followed by maize + cowpea + pumpkin, and the highest was maize + pumpkin. The TTS and Kupang varieties have the highest average growth and production, which shows their resistance to competition and stress in t’sen.